Modeling the impact of glacial runoff on fjord circulation and submarine melt rate using a new subgrid‐scale parameterization for glacial plumes. Issue 2 (12th February 2015) - Cowton, Tom; Slater, Donald; Sole, Andrew; Goldberg, Dan; Nienow, Peter
Abstract: The injection at depth of ice sheet runoff into fjords may be an important control on the frontal melt rate of tidewater glaciers. Here we develop a new parameterization for ice marginal plumes within the Massachusetts Institute of Technology General Circulation Model (MITgcm), allowing three‐dimensional simulation of large (500 km 2 ) glacial fjords on annual (or longer) time scales. We find that for an idealized fjord (without shelf‐driven circulation), subglacial runoff produces a thin, strong, and warm down‐fjord current in the upper part of the water column, balanced by a thick and slow up‐fjord current at greater depth. Although submarine melt rates increase with runoff due to higher melt rates where the plume is in contact with the ice front, we find that annual submarine melt rate across the ice front is relatively insensitive to variability in annual runoff. Better knowledge of the spatial distribution of runoff, controls on melt rate in those areas not directly in contact with plumes, and feedback mechanisms linking submarine melting and iceberg calving are necessary to more fully understand the sensitivity of glacier mass balance to runoff‐driven fjord circulation. Key Points: We present a method for parameterizing subglacial runoff in ocean models This is used to examine fjord circulation and glacier melt on annual time scales We find interannual runoff variability to have only limited impact on melt rate